P.O.P.P.I.Y.A Nestum / Che Ku Anis Farhana Che Ku Abu Bakar - Che Ku Abu Bakar, Che Ku Anis Farhana (2021)
The purpose of this report is to present my online business by finding a product and utilize Facebook (FB) for online marketing campaign. To carry out this assignment, I have to utilizing Facebook for marketing purposes by creating Facebook page and more. So, in this individual report, i have sell a product named P.O.P.P.I.Y.A Nestum by producing a teaser, soft sell, hard sell, and graphic for online marketing about my product to attract the customers. The main objective for the business is to offer a good quality homemade snack to be eaten and reasonable price that everyone can get. The business started 25 June 2021 by using media social platform to reach customers. My targeted customers are housewife, teenagers, students, and children. I am grateful since the beginning of my business, I received a lot of good feedback from the customers regarding my homemade snack. Other than self-pickup, we also offer delivery service (cod) for customers near to the business area. So far, P.O.P.P.I.Y.A NESTUM has been sold over 100 pack and it has been proven that P.O.P.P.I.Y.A Nestum is a good choice with a good quality of homemade snack for everyone to eat.